Increase in germination and plating efficiency of Neurospora crassa microconidia by amino acid supplementation - K Pitchaimani; S Sultan; R Maheshwari (Fungal Genetics Reports, 2000)
A major difficulty that has limited the use of uninucleate microconidia in genetic research is their low and erratic germination. We found that the supplementation of sorbose plating medium by amino acids, notably aspartic acid and methionine, markedly improved germination and plating efficiency of microconidia of mcm and pe fl genotypes of N. crassa. The plating efficiency of mcm microconidia in amino acid supplemented medium was comparable to macroconidia.